Dermatocosmetic Emulsions Based on Resveratrol, Ferulic Acid and Saffron (Crocus sativus) Extract to Combat Skin Oxidative Stress-Trigger Factor of Some Potential Malignant Effects: Stability Studies and Rheological Properties - Delia Turcov; Ana Simona Barna; Alexandra Cristina Blaga; Constanta Ibanescu; Maricel Danu; Adriana Trifan; Anca Zbranca; Daniela Suteu (MDPI AG, 2022)
The increasing incidence of skin diseases, against the background of increased pollution, urbanism, poor habits in lifestyle, work, rest, diet and general medication, led to the development of products with a protective effect. These new types of dermatocosmetic preparations ensure maximum benefits with minimal formulation. Antioxidants are, nowadays, ingredients that stand out with a proven role in skin protection from oxidative stress and its effects. Thus, research has shown that light-textured formulas, quickly absorbed into the skin, with optimum hydration and protection against excessive free radicals, uphold the skin integrity and appearance. This article aims to evaluate essential criteria for a newly marketed product: stability, rheological properties and microbiological characteristics of oil-in-water emulsions based on a mixture of 3% resveratrol 0.5% ferulic acid and 1mL alcoholic extract of Saffron. The tests led to the conclusion that O / W dermatocosmetic emulsions, based on 3% resveratrol and 0.5% ferulic acid, or also 1mL alcoholic extract of Saffron, show resistance to microbiological contamination, good rheological properties (viscoelastic behavior, structural stability, acceptable shearing behavior) that reveal satisfactory texture and high physical stability during storage. These results encourage the transition to dermatological testing as the final stage in considering a new commercial product.